2020
DOI: 10.1021/acs.biomac.0c01393
|View full text |Cite
|
Sign up to set email alerts
|

Multienzyme Cellulose Films as Sustainable and Self-Degradable Hydrogen Peroxide-Producing Material

Abstract: The use of hydrogen peroxide-releasing enzymes as a component to produce alternative and sustainable antimicrobial materials has aroused interest in the scientific community. However, the preparation of such materials requires an effective enzyme binding method that often involves the use of expensive and toxic chemicals. Here, we describe the development of an enzyme-based hydrogen peroxide-producing regenerated cellulose film (RCF) in which a cellobiohydrolase (TrCBHI) and a cellobiose dehydrogenase (MtCDHA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…However, as other studies have demonstrated that UV irradiation in combination with H 2 O 2 can trigger rapid self-destruction of cellulose materials, this approach could possibly also be utilized for the preparation of self-degradable cellulose films. 55 …”
Section: Degradation By Specific Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as other studies have demonstrated that UV irradiation in combination with H 2 O 2 can trigger rapid self-destruction of cellulose materials, this approach could possibly also be utilized for the preparation of self-degradable cellulose films. 55 …”
Section: Degradation By Specific Enzymesmentioning
confidence: 99%
“…H 2 O 2 producing enzymes, cellobiohydrolase and cellobiosedehydrogenase, have also been adsorbed on cellulose films aimed at antibacterial surfaces. However, as other studies have demonstrated that UV irradiation in combination with H 2 O 2 can trigger rapid self-destruction of cellulose materials, this approach could possibly also be utilized for the preparation of self-degradable cellulose films …”
Section: Degradation By Specific Enzymesmentioning
confidence: 99%
“…Biosourced rod-like colloids (RC) and rod-like polymers (RP) have excellent mechanical and optical properties and are often regarded as sustainable and biocompatible building blocks. These features have been exploited to form novel materials with applications in biomedical and food engineering. Classical examples of biosourced RC that can be produced in industrially relevant quantities comprise cellulose nanofibrils, cellulose nanocrystals, and protein nanofibrils. Nonetheless, these RC are characterized by a polydisperse contour length which complicates the prediction of their flow behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This approach enables us to continuously produce H2O2 without the need for external addition of cellobiose or glucose, achieving up to 170 μM which is higher that our previously reported quantity of 90 μM, using TthCDHIIa with cellobiose (Figure 25c). Similar approaches using celluloses disc chemically synthesized have been reported 39 .…”
Section: Part IImentioning
confidence: 68%
“…In the last two decades a growth in infections caused by drug-resistant and biofilmforming bacteria has been consistently reported 37,38 . CDH might play a role as an attractive antimicrobial and antibiofilm agent, due to its ability to continuously produce hydrogen peroxide from oligosaccharides like cellobiose, 39 which are not metabolizable by pathogens 40 . This non-canonical use of CDH and other enzymes in biomedical applications has been growing, as documented by several recent studies [41][42][43][44][45] .…”
Section: Searching For New Antibiofilm Agentsmentioning
confidence: 99%